2012
DOI: 10.1353/csd.2012.0010
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between University Students' Reported Reasons for Abstinence From Illicit Substances and Type of Drug

Abstract: We recruited 211 undergraduates to rate the degree to which each of 34 listed reasons for not taking drugs had influenced their abstinence from MDMA/ecstasy, cocaine, marijuana, and hallucinogens. Participants rated reasons such as personal and family medical histories, religion, and physiological consequences of drug use as having little or no impact on abstention from all four substances. Consistent with previous research and developmental theory, concerns about drug-induced impairment and drug use being con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…High-risk adolescents (i.e., those evidencing behavioral, emotional, or substance use problems) cite avoidance of legal and employment consequences as their primary reasons to stop using marijuana (Weiner, Sussman, McCuller, & Lichtman, 1999). In a study of college-aged marijuana abstainers, highly influential reasons for abstinence included, “It does not fit the image I have of myself,” “I don’t need it to have a good time,” and “I don’t see benefits of using it” (Rosenburg et al, 2012, p. 98). The assumption of adult social roles (e.g., having children, getting married, launching a new career) is commonly associated with cessation from marijuana use (Chen & Kandel, 1998; Hammer & Vaglum, 1990).…”
mentioning
confidence: 99%
“…High-risk adolescents (i.e., those evidencing behavioral, emotional, or substance use problems) cite avoidance of legal and employment consequences as their primary reasons to stop using marijuana (Weiner, Sussman, McCuller, & Lichtman, 1999). In a study of college-aged marijuana abstainers, highly influential reasons for abstinence included, “It does not fit the image I have of myself,” “I don’t need it to have a good time,” and “I don’t see benefits of using it” (Rosenburg et al, 2012, p. 98). The assumption of adult social roles (e.g., having children, getting married, launching a new career) is commonly associated with cessation from marijuana use (Chen & Kandel, 1998; Hammer & Vaglum, 1990).…”
mentioning
confidence: 99%
“…Furthermore, the MTF survey did not contain questions on reasons for abstaining from other substances. Considering that certain abstinence motives may to be unique to marijuana and others are shared across multiple substances (Rosenberg et al, 2012), future research is needed to examine how reasons for non-use may differ by type of substance and the extent to which those reasons contribute to future use.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Yo uth who intend to stop using marijuana have been found to report legal and employment problems as key reasons to stop use (Weiner et al, 1999) and perceive marijuana use as a detriment to their self-image (Rosenberg et al, 2012). Terry-McElrath et al (2008) examined the extent to which national cross-sectional samples of high school seniors from the Monitoring the Future (MTF) study reported various categories of reasons for marijuana non-use and also examined differences in reasons reported by high school seniors with and without prior marijuana use.…”
mentioning
confidence: 99%
“…Moreover, reasons to abstain from taking alcohol or drugs among university students are the perception that it will result in unwanted reduced control over emotions and behaviour, and a perceived lack of benefits of substance use [12]. The perception that substance use is harmful and potentially addictive is indeed one of the most relevant factors affecting youth substance use [13].…”
Section: Introductionmentioning
confidence: 99%